Chandra Observations of Galaxy Zoo Mergers: Frequency of Binary Active Nuclei in Massive Mergers - Teng, S; Schawinski, K; Urry, C; Darg, D; Kaviraj, S; Oh, K; Bonning, E; Cardamone, C; Keel, W; Lintott, C; Simmons, B; Treister, E (Institute of Physics Publishing, 2012)
We present the results from a Chandra pilot study of 12 massive galaxy mergers selected from Galaxy Zoo. The sample includes major mergers down to a host galaxy mass of 10$^{11}$ $M_\odot$ that already have optical AGN signatures in at least one of the progenitors. We find that the coincidences of optically selected active nuclei with mildly obscured ($N_H \lesssim 1.1 × 10^{22}$ cm$^{-2}$) X-ray nuclei are relatively common (8/12), but the detections are too faint ($< 40$ counts per nucleus; $f_{2-10 keV} \lesssim 1.2 × 10^{-13}$ erg s$^{-1}$ cm$^{-2}$) to reliably separate starburst and nuclear activity as the origin of the X-ray emission. Only one merger is found to have confirmed binary X-ray nuclei, though the X-ray emission from its southern nucleus could be due solely to star formation. Thus, the occurrences of binary AGN in these mergers are rare (0-8%), unless most merger-induced active nuclei are very heavily obscured or Compton thick.